Serial testing of Mycobacterium tuberculosis infection in Chinese village doctors by QuantiFERON-TB Gold Plus, QuantiFERON-TB Gold in-Tube and T-SPOT.TB. Issue 4 (April 2019) - Zhang, Haoran; Xin, Henan; Wang, Dakuan; Pan, Shouguo; Liu, Zisen; Cao, Xuefang; Wang, Jinxing; Li, Xiangwei; Feng, Boxuan; Li, Mufei; Yang, Qianting; Zhang, Mingxia; et al.
Summary: Objectives: To evaluate the performance of QuantiFERON-TB Gold Plus (QFT-Plus) on Mycobacterium tuberculosis (MTB) infection test among registered village doctors from China. Methods: MTB infection of the registered village doctors in Zhongmu County were tested using QFT-Plus and two other interferon-gamma release assays (IGRAs) in parallel: QuantiFERON-TB Gold In-Tube (QFT) and T-SPOT.TB (T-SPOT). Retests were carried out for baseline positives at 3 and 6 months later, respectively. Results: A total of 616 village doctors were included in the baseline examination. The positivity of QFT, QFT-Plus and T-SPOT was 27.91% (168/602), 31.22% (187/599) and 27.70% (169/610), respectively. The concordance between QFT and QFT-Plus was 94.81% (Kappa coefficient: 0.87) and between T-SPOT and QFT-Plus was 88.93% (Kappa coefficient: 0.73). Reversions were frequently observed for all three assays. With respect to QFT-Plus, the quantitative results of reversions in the serial testing were mostly distributed in an "uncertain range" zone (0.2-0.7 IU/mL). Similar patterns of distribution were observed for QFT and T-SPOT as well. Conclusion: Village doctors should gain more attention as an at-risk group for TB infection control in rural China. Our results support, by means of serial testing, a good agreement between QFT-Plus and QFT in Chinese population.